The Role of Wholesalers in International Distribution: Transaction Cost Effects - Tamara Todorova; Ivan Iliev (Logistics in the Transition Economy. Papers from the Second International Conference "Logistics in the Changing World" (Theory, Practice, Education), Varna, July 12-13, 1999, 1999)
The paper focuses on the role of wholesaling in the establishment of international distribution channels with respect to the transaction costs associated with the sale of goods on the international market. The first part of the paper is devoted to the peculiarities and conditions of the domestic market and the participation in it of domestic wholesalers. The main idea is that of the necessity of wholesaling in terms of transaction cost reduction. A model is presented revealing a distribution channel with and without an intermediary as a link between the producers and the retailers. The paper argues that wholesalers have a vital role in bringing down the costs of transacting as well as in the proper and efficient functioning of the very distribution channel. The second part of the paper discusses the international market in its complexity and size compared to local markets. This is done in the context of the transaction costs faced by large international corporations. The focus is again on these costs which turn out to be the reason for firms to internalize their market operations expanding thus their size.
Additional information: In memory of Associate Professor Ivan Iliev.
Keywords: D23; F18; M21; M31; 330; transaction costs; wholesaling; international distribution